Integration of Indigenous Knowledge and Modern Science: An Ethnopharmacological Study of Lansano (Pterocarpus indicus Willd.) as a Traditional Medicine in West Sumatra - Nurhasnah; Media Roza; Lince Meriko; Indah Kencanawati; Lufri; Abdul Razak (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2025)
This study explores ethnoscientific practices surrounding Lansano (Pterocarpus indicus Willd.), a medicinal plant traditionally used in West Sumatra, Indonesia. Qualitative ethnographic methods, including direct observation and semi-structured interviews, were used with 50 respondents from various regions, including Padang, Pariaman, Solok, Sijunjung, Pasaman, Padang Panjang, and Pesisir Selatan. Participants included local healers, herbal practitioners, and community members known to use Lansano for medicinal purposes. This study employed a quantitative ethnobotanical approach with two main parameters: Use Value (UV) and Informant Consensus Factor (ICF). This study revealed a significant relationship between traditional practices and scientific evidence in the use of Lansano as an herbal medicine. This study is the first step in integrating Lansano ethnobotanical practices with bioactive data for the development of local culture-based phytopharmaceuticals. Use Value (UV) analysis showed that the leaves had the highest utilization value (UV = 0.70), followed by the roots (0.44), sap (0.36), and stems (0.30). Meanwhile, Informant Consensus Factor (ICF) analysis showed a complete consensus (ICF = 1.00) among informants regarding the use of lansano for various ailments, with the highest frequency of use for mouth ulcers, followed by diarrhea, menstrual pain, and burns. These results confirm that lansano has high ethnopharmacological value and is widely believed to be a primary traditional medicine in West Sumatra.